2003
DOI: 10.1021/ja021158h
|View full text |Cite
|
Sign up to set email alerts
|

β-Octafluorocorroles

Abstract: The one-pot corrole synthesis first reported by the Gross and Paolesse groups appears to have evolved into a remarkably general and predictable self-assembly based synthetic reaction. Gross's solvent-free procedure (refs 8 and 9) has proven particularly effective in our hands and, in fact, more general than originally claimed. In earlier work (ref 17), we showed that the reaction works for a variety of aromatic aldehyde starting materials and was not limited to relatively electron-deficient aldehydes, as repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
110
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 43 publications
14
110
0
2
Order By: Relevance
“…Although these substituents significantly change the redox properties of the complexes, our results indicate that the electronic structures are analogous to those calculated for the unsubstituted chloroiron corroles with electron-rich corrole ligands, in line with the studies on the chloroiron b-octafluorocorrole complex. [38] Mçssbauer spectroscopy alone is not able to unambiguously discriminate between the two alternative formulations: low-spin iron(IV) chelated by a closed-shell corrolato trianion versus intermediate-spin…”
Section: Resultsmentioning
confidence: 99%
“…Although these substituents significantly change the redox properties of the complexes, our results indicate that the electronic structures are analogous to those calculated for the unsubstituted chloroiron corroles with electron-rich corrole ligands, in line with the studies on the chloroiron b-octafluorocorrole complex. [38] Mçssbauer spectroscopy alone is not able to unambiguously discriminate between the two alternative formulations: low-spin iron(IV) chelated by a closed-shell corrolato trianion versus intermediate-spin…”
Section: Resultsmentioning
confidence: 99%
“…[1] In other words, copperc orroles have as ubstantial Cu II -corroleC 2À character.T he strength of the metal-corrole spin coupling varies from weak, as reflected in thermally accessible triplets tates for simple coppert riarylcorroles, to quite strong for the most strongly saddledc omplexes. [1,3,4,5,9,10] Gold(III) corroles by contrasta re innocent and relatively planar, regardless of the degree of peripheral steric hindrance. [11][12][13] The difference between copperand gold was strikingly illustrated in crystallographic studies of highly sterically hindered b-octakis(trifluoromethyl)-meso-triarylcorrole complexes, in which the copper complex was found to be extremely saddled, [4] with adjacent pyrrole rings essentially orthogonal to one another,w hile the gold complext urned out to be perfectly planar.…”
Section: Introductionmentioning
confidence: 99%
“…[91] Moreover, we found that 3,4-difluoropyrrole reacts with a variety of para-substituted benzaldehydes to yield the corresponding b-octafluoromeso-tris(p-XC 6 H 4 )corroles (X = CF 3 , H, CH 3 , or OCH 3 ; Scheme 14). [92] Interestingly, no condensation of 3,4-difluoropyrrole with pentafluorobenzaldehyde took place to produce perfluorinated triphenylcorrole ((F 8 TPFC)H 3 ). Chang and co-workers also failed to isolate (F 8 TPFC)H 3 by using the original conditions of the one-pot corrole synthesis.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Our general one-pot "solvent-free" corrole synthesis, including the synthesis of a family of b-octafluoro-meso-triaryl corroles. [91,92] Shown against the green background is perfluorinated triphenylcorrole ((F 8 TPFC)H 3 ), recently prepared by Chang and co-workers. [93] Angewandte Chemie A. Ghosh relatively long period of heating in the solvent-free procedure also led to the formation of (F 8 TPFC)H 3 in a low but acceptable yield of 5 %.…”
Section: Angewandte Chemiementioning
confidence: 99%